The Role of Operation in the Treatment of Boerhaave's Syndrome. (28th June 2018) - Han, Dingpei; Huang, Zhuoqiong; Xiang, Jie; Li, Hecheng; Hang, Junbiao
Abstract : Purpose. This study aims to discuss the appropriate treatment strategy for spontaneous esophageal rupture. Methods. Clinical data from twenty-one cases were retrospectively analyzed. The parameters included etiology, time interval between onset and treatment, therapy methods, prognosis, and length of stay. Results. The ratio of males/females was 17/4, age range was 32–82 years (mean = 43.1), and the time interval between onset and treatment was as follows: <24 h: nine cases (42.8%); 24–48 h: six cases (28.6%); and >72 h: six cases (28.6%). All patients underwent operative treatment, and the following primary healing rates were achieved: <24 h: 88.9%, 24–48 h: 66.7%, and >72 h: 0. No patients died in this study. All patients were discharged with recovery, and the average hospitalization times were 18.1 days (<24 h), 27.8 days (24–48 h), and 51.2 days (>72 h). Conclusions. Surgical treatment remains an effective method for treating spontaneous esophageal rupture, and the shorter the time interval between onset and treatment, possibly the better the prognosis.